2004
DOI: 10.1155/2004/348028
|View full text |Cite
|
Sign up to set email alerts
|

1H MRS phantom studies of BNCT 10B‒carrier, BPA–F using STEAM and PRESS MRS sequences: Detection limit and quantification

Abstract: The quantification of boron neutron capture therapy (BNCT)10B‒carrier, L‒p‒boronophenylalanine‒fructose complex (BPA–F) was studied with phantoms using1H magnetic resonance spectroscopy sequences PRESS and STEAM at 1.5 and 3.0 T. The results show that typical attainable short echo times of clinical MRS sequences combined with long repetition time result in clinically acceptable quantification accuracy. However, the concentration ratios, which are essential for the treatment planning, can still be reliably meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…One of the problems confronting the successful clinical implementation of BNCT is the difficulty of quantitatively mapping the distribution of the boron containing molecules in patients during the treatment. [57][58][59] Furthermore, the clinical efficacy of the therapy is only guaranteed if the boron is located inside a tumor cell at a concentration of at least 20-30 ppm.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the problems confronting the successful clinical implementation of BNCT is the difficulty of quantitatively mapping the distribution of the boron containing molecules in patients during the treatment. [57][58][59] Furthermore, the clinical efficacy of the therapy is only guaranteed if the boron is located inside a tumor cell at a concentration of at least 20-30 ppm.…”
Section: Discussionmentioning
confidence: 99%
“…One of the problems is that the uptake and distribution of 10 B varies among patients and that large uncertainties exist in the tumor-to-blood 10 B concentration ratio. 57,58,84 At the same time the selective delivery of the NCT agent becomes one of the crucial points for the success of the treatment and only two compounds (BPA and BSH) have been extensively tested in both pre-clinical and clinical trials. Only proper NCT agent design, based on an improved knowledge of how molecules enter healthy and diseased cells, could allow the minimal intracellular concentration, needed to make NCT an effective therapy to cure cancer, to be reached.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The possibility of detecting the aromatic BPA protons was recognized previously and demonstrated on a patient using standard STEAM (TE = 30 ms) (3). Subsequent studies characterized the echo‐time dependence of the aromatic proton BPA signals in aqueous solutions for STEAM and PRESS sequences (4, 5). As expected, these studies demonstrated the considerable modulation of the signal due to J ‐coupling, causing both phasing and signal loss problems and stressing the need for efficient, short‐TE sequences.…”
mentioning
confidence: 99%